1987
DOI: 10.1523/jneurosci.07-11-03793.1987
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative distribution of the glycine receptor in the auditory brain stem of the gerbil

Abstract: The concentration and relative distribution of glycine receptors were determined for gerbil brain stem auditory nuclei using 3H-strychnine and quantitative autoradiographic techniques. Significant binding was observed in the anteroventral cochlear nucleus, the dorsal cochlear nucleus, the lateral superior olivary nucleus, and the inferior colliculus. A non-uniform distribution of binding was seen in 3 of these nuclei, such that the greatest concentration of glycine receptors was located in the high-frequency r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(46 citation statements)
references
References 54 publications
4
41
1
Order By: Relevance
“…The projection from the MNTB to the ipsilateral LSO (Spirou et al, 1990) is inhibitory and uses glycine as neurotransmitter. Numerous studies have demonstrated both a-subunit receptor immunoreactivity (Aoki et al, 1988) and high binding of 'H-strychnine in the LSO (Sanes et al, 1987;Glendennig and Baker, 1988). Electrophysiological data have shown the presence of strychnine-sensitive synapses in the LSO (Moore and Caspary, 1983;Wu and Kelly, 1991).…”
Section: Glycine Transporters In Glycinergic Nellrotransmissionmentioning
confidence: 99%
“…The projection from the MNTB to the ipsilateral LSO (Spirou et al, 1990) is inhibitory and uses glycine as neurotransmitter. Numerous studies have demonstrated both a-subunit receptor immunoreactivity (Aoki et al, 1988) and high binding of 'H-strychnine in the LSO (Sanes et al, 1987;Glendennig and Baker, 1988). Electrophysiological data have shown the presence of strychnine-sensitive synapses in the LSO (Moore and Caspary, 1983;Wu and Kelly, 1991).…”
Section: Glycine Transporters In Glycinergic Nellrotransmissionmentioning
confidence: 99%
“…In bats, GABA A and glycine receptors are reported to have either opposing gradients of distribution, in which GABA A receptors are densest dorsalmedial, and glycine ventral-lateral, or an even distribution of GABA A receptors, with glycine receptors confined mainly to the ventral-lateral region (Fubara et al 1996;Vater et al 1990;Winer et al 1995). A similar glycine receptor distribution is seen in the gerbil (Sanes et al 1987). A physiological corollary is that the effects of blocking glycine are seen only in deeper regions of the IC (Koch and Grothe 1998;Lu and Jen 2001).…”
mentioning
confidence: 92%
“…Although the types of synaptic receptors that mediate excitatory and inhibitory synaptic transmission in the ICC have been identified by immunocytochemical labeling, receptor binding, physiological recording, and the use of pharmacological agents (Sanes et al, 1987;Petralia and Wenthold, 1992;Winer et al, 1995;Fubara et al, 1996;Wagner, 1996; Gaza and Ribak, 1997; Moore et al, 1998;Caicedo and Eybalin, 1999;Ma et al, 2002a,b), little is known about how activation of receptors influences temporal processing in ICC neurons. In this study, we recorded the postsynaptic responses to repetitive stimulation of the lateral lemniscus and examined the effects of AMPA, NMDA, and GABA A receptor antagonists.…”
Section: Introductionmentioning
confidence: 99%